Molecular characterization of Brucella species from Zimbabwe. - Maphuti Betty Ledwaba; Calvin Gomo; Kgaugelo Edward Lekota; Philippe Le Flèche; Ayesha Hassim; Gilles Vergnaud; Henriette van Heerden (Public Library of Science (PLoS), 2019)
Brucella abortus and B. melitensis have been reported in several studies in animals in Zimbabwe but the extent of the disease remains poorly known. Thus, characterizing the circulating strains is a critical first step in understanding brucellosis in the country. In this study we used an array of molecular assays including AMOS-PCR, Bruce-ladder, multiple locus variable number tandem repeats analysis (MLVA) and single nucleotide polymorphisms from whole genome sequencing (WGS-SNP) to characterize Brucella isolates to the species, biovar, and individual strain level. Sixteen Brucella strains isolated in Zimbabwe at the Central Veterinary laboratory from various hosts were characterized using all or some of these assays. The strains were identified as B. ovis, B. abortus, B. canis and B. suis, with B. canis being the first report of this species in Zimbabwe. Zimbabwean strains identified as B. suis and B. abortus were further characterized with whole genome sequencing and were closely related to reference strains 1330 and 86/8/59, respectively. We demonstrate the range of different tests that can be performed from simple assays that can be run in laboratories lacking sophisticated instrumentation to whole genome analyses that currently require substantial expertise and infrastructure often not available in the developing world.